Assessment of Electric and Magnetic Field Exposure Near Overhead Transmission Lines Using 2D Finite Elements Method - Glushica, Bojan; Markovski, Blagoja; Kuhar, Andrijana; Arnautovski-Toseva, Vesna (Symposium on Applied Electromagnetics, 2022)
Electric and magnetic fields near power lines are of particular interest in safety analysis related to effects on the environment, human exposure and electromagnetic disturbances on adjacent systems. Electromagnetic modeling is an efficient procedure to assess their effects in different scenarios. In this paper we perform numerical analysis of the distribution of electric and magnetic fields in the vicinity of 110 and 400 kV overhead transmission lines using the open source software FEMM 4.2. The modelling procedure is briefly described and the results are verified using full-wave electromagnetic model based on the method of moments. Different configurations of transmission lines and the effects of phase sequence transposition are considered. Calculated electric and magnetic field levels are then compared to exposure limits established by ICNIRP. Using the magnetic field, the induced currents within fictional human tissue are also estimated.
Keywords: Electric field; Magnetic field; ICNIRP; FEMM; Transmission line